Pengaruh Model Brain Based Learning terhadap Pembentukan Karakter Siswa di Sekolah Dasar - Maya Muizatil Lutfillah; Asep Supena; Zulhendri Zulhendri (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2022)
The Brain Based Learning (BBL) learning model builds students' knowledge based on the cognitive structure they already have and is based on how the brain works so that learning can be absorbed by the brain optimally. This study aims to determine the effect of the BBL model on the formation of students' character in elementary schools. Building character is an obligation not only at birth, but when the baby is in the womb. In addition, teachers, especially in elementary schools, have the same obligation in shaping character. In the process, teachers need to use a brain-based character education approach (neuroscience). This research uses qualitative research which is based on literature review. Based on the results of the study, it was found that quality education is education that is able to shape the character of its students. Character education is more effective if it uses a brain approach (neuroscience), because changing character begins with changing students' brains.